Assessment of the interface shear strength between HDPE geomembrane and tropical soil by the direct shear test - da Costa, Sergio Luiz [UNESP]; Lodi, Paulo Cesar [UNESP] (My University, 2018)
Liners are important impermeable constituents of sanitary landfill to contain the transport of pollutants to the unsaturated zone. The system can be made of different kind, being the compacted soil and geosynthetics widely used. Thus, knowing the interface shear strength of those materials is important to avoid rupturing the system. The purpose of this paper is to compare the shear strength in the geomembrane-soil interfaces by the direct shear test. Assays were performed under the saturated condition (water and leachate). The used soil is a colluvial, lateritic, tropical silty sand-clay, typical of the city of Campinas, in Brazil. In this work, high density polyethylene (HDPE) 2,00mm geomembrane, smooth and two texturized – with different roughness level - were used. It was found that the shear strength is directly influenced by the roughness of the geomembrane, showed higher friction angle in the textured geomembrane. The direct shear test, performed with soil contaminated by leachate showed smaller friction angle than uncontaminated soil.
Keywords: Friction angle; Geomembrane; Interface shear strength; Leachate; Sanitary landfill